Kajian Yuridis Terhadap Penguasaan Tanah Secara Melawan Hukum - Mahendra, Resa; Karim, Kairuddin; Syahril, Muh. Akbar Fhad (Jurnal Litigasi Amsir, 2023)
This study aims to find out the basic material legal considerations of the Court Judge in deciding the case Case Number 2/Pdt.G/2020/PN.Sdr and to find out the application of the Judge’s Law in Case 2/Pdt.G/2020/PN. Sdr. The research method used in this writing is the type of research used in this research is normative research. Normative legal research is research conducted using an approach to legal norms or substances, legal principles, legal theory, legal arguments and comparative law, where the orientation of normative legal research is Law In Books, namely observing legal reality in various legal norms or rules that have formed. The results of the study show Legal considerations of unlawful acts disputes in the Sidenreng Rappang District Court Decision, occurred because of the transfer of land rights carried out by Hj. Nurliah Kamal committed an unlawful act against her over the object of the dispute, by making a Death Certificate from her family on behalf of H. P. Dali, and a Death Certificate on behalf of H. P. Camming, marked T-3; over the object of dispute which is used as evidence, but cannot be recognized as legal evidence of ownership by the Sidenreng Rappang District Court by taking into account the provisions of Article 163 HIR/283 RBg, the Civil Code, and all laws and regulations related to a case; Application of the Judge’s law in Mastery of the disputed object Stating according to law that the actions of the Defendant controlling the land of the object of dispute belonging to the Plaintiff and not wanting to hand over the object of dispute to the Plaintiff are unlawful acts, according to the Decision of the Sidenreng Rappang District Court Number 2/Pdt.G/2020/PN.Sdr.